Systematic Literature Review: Tren Penelitian Problem Based Learning dalam Meningkatkan Kemampuan Pemecahan Masalah Matematis - Laila Rahmawati; Eko Andy Purnomo; Venissa Dian Mawarsari (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Problem-solving ability is an essential competency in mathematics learning because it forms the foundation for developing critical, logical, and innovative thinking skills. Therefore, research on its development is of great importance. This study aims to systematically describe research trends in the application of the Problem-Based Learning (PBL) model to improve students’ mathematical problem-solving skills. The approach used is a Systematic Literature Review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 25 articles that met the inclusion and exclusion criteria were analyzed based on publication year, educational level, research subjects, and research methods. The findings show that publications from 2021 to 2025 fluctuate, with 2 (8%), 7 (28%), 5 (20%), 8 (32%), and 3 (12%) articles, respectively. Based on the educational level, 9 (36%) studies were conducted at the elementary level, 10 (40%) at the junior high school level, 5 (20%) at the senior high school/vocational level, and 1 (4%) at the university level. Regarding research subjects, 24 (96%) articles involved students and 1 (4%) involved university students. In terms of methodology, quantitative research was more dominant than qualitative, with 17 (68%) using quantitative approaches and 8 (32%) using qualitative ones. Overall, the SLR results indicate that studies on the implementation of the PBL model in mathematical problem-solving are predominantly quantitative, mostly conducted at the elementary and junior high school levels, and exhibit fluctuating publication trends from 2021 to 2025. Future research is recommended to expand educational levels, diversify research subjects, and combine various methodological approaches for more comprehensive findings.